Fostering Youth Entrepreneurship Through Community Engagement: A Case Study in Palawan, Philippines - Hidayah, Nur; Maryani, Ika; Sulisworo, Dwi (The Indonesian Institute of Science and Technology Research, 2025)
Entrepreneurship plays a crucial role in sustainable economic development, particularly in equipping young people with the skills needed to foster economic independence and contribute to the Sustainable Development Goals (SDGs). This study examines the impact of a community engagement initiative aimed at increasing youth awareness of entrepreneurship through structured training sessions. The training involved 50 student participants and covered fundamental entrepreneurial concepts, business strategies, and innovation. Methods employed included presentation sessions, case studies, interactive discussions, and business simulations. The effectiveness of the program was assessed through Q&A sessions, revealing a significant increase in participants’ understanding and interest in entrepreneurship. The findings highlight the importance of fostering entrepreneurial skills in youth as a means of addressing global economic challenges and promoting sustainable development. Expanding similar initiatives can further encourage young entrepreneurs to drive economic resilience and innovation.